Having a Baby: Impact on Married and Cohabiting Parents' Relationships. Issue 2 (18th July 2020) - O'Reilly Treter, Maggie; Rhoades, Galena K.; Scott, Shelby B.; Markman, Howard J.; Stanley, Scott M.
Abstract : The current study evaluates the effects of having a baby on relationship quality and stability, contrasting married and unmarried cohabiting parents ( N = 179; 38% unmarried cohabiting). Participants provided several waves of data, including time points before, during, and after pregnancy. Results indicated that cohabiting parents broke up at a significantly higher rate after having a baby compared to married parents. In terms of relationship quality, interrupted time‐series analyses indicated that negative communication significantly increased after baby regardless of marital status. In addition, married parents had significantly higher levels of relationship satisfaction and commitment before baby compared to cohabiting parents but experienced modest declines in relationship satisfaction after baby. Cohabiting parents did not show such declines but remained lower in satisfaction throughout the study. Gender moderated commitment trajectories, such that married and cohabiting women demonstrated decreased commitment after baby, but married and cohabiting men demonstrated no significant changes in commitment. This study adds to the literature by examining both relationship stability and relationship quality trajectories from before pregnancy to after the birth of a baby among married and cohabiting parents in the same sample. Implications of these findings for practice and future research are discussed. RESUMEN: El presente estudio evalúa los efectos de tener un bebé en la calidad y la estabilidad de la relación, contrastando los padres casados y los concubinos convivientes ( N = 179; 38 % concubinos convivientes). Los participantes proporcionaron varias series de datos que incluyeron momentos antes, durante y después del embarazo. Los resultados indicaron que los padres concubinos se separaron a un índice considerablemente mayor después de tener un bebé en comparación con los padres casados. En cuanto a la calidad de la relación, los análisis de series de tiempo interrumpido indicaron que la comunicación negativa aumentó considerablemente después del bebé independientemente del estado civil. Además, los padres casados tuvieron niveles considerablemente más altos de satisfacción con la relación y de compromiso antes del bebé en comparación con los padres concubinos, pero tuvieron leves reducciones de la satisfacción con la relación después del bebé. Los padres concubinos no demostraron esas disminuciones pero mantuvieron una satisfacción más baja a lo largo del estudio. El género moderó las trayectorias de compromiso, de manera que las mujeres casadas y las concubinas demostraron un menor compromiso después del bebé, pero los hombres casados y los concubinos no demostraron cambios significativos en el compromiso. Este estudio enriquece la bibliografía analizando tanto las trayectorias de estabilidad de la relación como de calidad de la relación desde antes del embarazo hasta después del nacimiento de un bebé entre padres casados y padres concubinos en la misma muestra. Se debaten las consecuencias de estos resultados para la práctica y las futuras investigaciones. 摘要: 本研究评估了生养孩子对夫妻关系质量和稳定性的影响，把已婚父母和未婚同居父母(总数 = 179; 38%的未婚同居)进行对比。参与者提供了几波数据，包括怀孕前、怀孕期间和怀孕后等不同时间点的情况。结果显示，与已婚父母相比，同居父母在生完孩子后分手的比例要高得多。在关系质量方面，通过间断的系列时间点的情况分析表明，无论婚姻状况如何，在婴儿出生后夫妻之间负面的沟通显著增加。此外，与同居父母相比，已婚父母在孩子出生前对婚姻关系的满意度和恪守承诺的投入程度明显更高。但在孩子出生后，已婚父母对婚姻关系的满意度则略有下降。在整个研究过程中，同居父母并没有表现出这种下降趋势，不过他们对婚姻的满意度相对而言始终保持较低水平。性别的不同也反应出在婚姻方面投入的程度变化轨迹的差异，例如已婚和同居的女性在生完孩子后婚姻关系投入水平表现出逐减的趋势，而已婚和同居的男性在婚姻关系上没有显著的变化。本文研究了同一样本中已婚和同居父母从怀孕前到孩子出生后的关系稳定性和关系质量变化的轨迹。此研究增加了现有的研究文献，文中也讨论了研究发现对实践和未来研究的意义。